2019
DOI: 10.23865/up.v13.1970
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ regard for adolescent perspectives in feedback dialogues with students in lower-secondary schools

Abstract: The teacher is a key agent in facilitating for adolescent perspectives during lessons. Feedback dialogues have an inherent capacity to capitalise on or undervalue adolescent perspectives in instruction and learning. The present study focused on lower-secondary school teachers’ regard for adolescent perspectives in feedback dialogues with students in lessons on English as a foreign language (EFL, n = 65) and mathematics (n = 113). The data material consisted of video recordings coded with the regard for adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Emotions imported from outside the classroom affected how feedback was experienced by students, with negative emotions blocking the receipt of teacher feedback (Kerr, 2017). Vattøy and Gamlem (2019) found their teacher participant who had a high regard for adolescent perspective was able to elicit information that a student was distracted by negative feelings about a chore he had failed to complete at home. Such attention was an opportunity to build mutual trust and respect and eased the process of teacher redirection.…”
Section: Results By Dimension Of Student Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Emotions imported from outside the classroom affected how feedback was experienced by students, with negative emotions blocking the receipt of teacher feedback (Kerr, 2017). Vattøy and Gamlem (2019) found their teacher participant who had a high regard for adolescent perspective was able to elicit information that a student was distracted by negative feelings about a chore he had failed to complete at home. Such attention was an opportunity to build mutual trust and respect and eased the process of teacher redirection.…”
Section: Results By Dimension Of Student Experiencementioning
confidence: 99%
“…Typically, teachers overestimated how active students were in dialogic processes (Jónsson et al, 2018;van der Kleij, 2019). Although some studies identified feedback loops between students and teachers, 'quality' loops that expand and extend students' learning over time were few (Gamlem & Munthe, 2014;Peterson & Irving, 2008;Vattøy & Gamlem, 2019). This is explained by: students having limited time for using feedback (Burner, 2016;Xiao, 2017); failing to understand feedback (Lee, 2007); or teachers' overtaking interactions, like goal-setting for students, thus diffusing the intended effect of the practice (Charteris & Smardon, 2018).…”
Section: Dimension 5: Active and Interactive Responses (N = 62)mentioning
confidence: 99%
“…Teacher sensitivity (TS) is when an instructor consistently monitors students for cues needing extra support or assistance (Kennedy, 2019). Lastly, adolescent perspective (RAP) can be understood as the degree to which instructors emphasize perspectives concerning exibility, connections to the current life, support for autonomy and leadership, and meaningful peer interactions (Vattøy and Gamlem, 2019). Generally, these dimensions are crucial in promoting students' learning motivation and engagement (Ruzek et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%